Desired Versus Actual Training for Online Instructors in Community Colleges - Pagliari, Leslie; Batts, David; McFadden, Cheryl C. (East Carolina University, 2009)
The growth of distance education and the demand for instructors has developed over the past ten to fifteen years. There is a perception that the type and amount of instructor preparation is highly variable between institutions. Of the faculty members at two year institutions surveyed, nearly half did not attend training over the previous year. With technology changing rapidly, there is a need for training annually to assure faculty members who teach online are prepared. Distance education administrators need to evaluate their distance education programs and develop a consistent and current infrastructure to assure that their faculty members are being properly trained to teach online.
Keywords: Online education; Faculty development; Distance education; Instructor preparation